Numerical analysis theory and experiments - Sutton, Brian (Brian David) (Other titles in applied mathematics, 2019)
This textbook develops the fundamental skills of numerical analysis: designing numerical methods, implementing them in computer code, and analyzing their accuracy and efficiency. A number of mathematical problems--interpolation, integration, linear systems, zero finding, and differential equations--are considered, and some of the most important methods for their solution are demonstrated and analyzed. Notable features of this book include the development of Chebyshev methods alongside more classical ones, a dual emphasis on theory and experimentation, the use of linear algebra to solve problems from analysis, which enables students to gain a greater appreciation for both subjects, and many examples and exercises